Resistensi Tertutup Perempuan Jawa pada Budaya Patriarki pada Visual dan Komponen Film Kartini (2017) - Nurudin Sidiq Mustofa; Rony Ramadhan (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2024)
Patriarchy, a system where men dominate, has long influenced society, including the notion that women are weaker. However, the spirit of resistance is increasingly echoed, including through media such as movies. This article aims to explore the traces of closed resistance to patriarchal culture in film, using the movie "Kartini" as an example. This research analyzes "Kartini" qualitatively, going scene by scene to find John Fiske's three-tingkat "social codes". These codes, ranging from the surface tingkat to the underlying reality, help reveal the hidden messages in the movie. The closed resistance to patriarchy is implied in the movie's visuals and various other components, from the costumes Kartini wears to the cinematography used.  Through this analysis, we can see that film can be a powerful weapon against patriarchal culture. "Kartini" shows how Javanese women, despite living in the shackles of custom, can resist and fight for their rights.